Atypical presentation and clinical management of jaundice secondary to Choledocoduodenal fistula: A Case Report (South East Asia Journal of Public Health, 2017)
Choledocoduodenal fistula (CDDF) is an abnormal connection between the common bile duct and the duodenum which bypasses the normal opening of Ampulla of Vater. In this case, we describe the initial clinical presentation, diagnosis and treatment of a patient with CDDF along with prophylactic surgical management in order to prevent future hepatobiliary complications. In addition, we also discuss various risk factors of CDDF. Finally, we also discuss different types of CDDF along with its various hematologic and radiologic findings.South East Asia Journal of Public Health Vol.7(1) 2017: 55-57